Melicopteline A-E, Unusual Cyclopeptide Alkaloids with Antiviral Activity against Influenza A Virus from Melicope pteleifolia - Lee, Ba Wool; Ha, Thi Kim Quy; Park, Eun Jin; Cho, Hyo Moon; Ryu, Byeol; Doan, Thi Phuong; Lee, Hee Ju; Oh, Won Keun (AMER CHEMICAL SOC, 2021)
In the search for antiviral cyclopeptides against influenza A virus, five unprecedented Caryophyllaceae-type cyclopeptides (1-5) were isolated from the leaves of Melicope pteleifolia. Their chemical structures and absolute configurations were unambiguously determined by means of advanced Marfey's analysis and comprehensive spectroscopic analyses including two-dimensional nuclear magnetic resonance and MS/MS fragmentation. Interestingly, compounds 3-5 contain an unusual heterocycle, a 3a-hydroxypyrroloindole moiety, which was biosynthetically formed by a nucleophilic cyclization from the least abundant amino acid, tryptophan, precursor and has aroused a great interest in the aspect of chemical diversity and biological activity. All isolates (1-5) were evaluated for their protective effects against influenza A viruses H1N1 and H9N2 in MDCK cells. All isolated cyclopeptides exhibited strong anti-influenza activity, especially against H1N1. Compound 3 showed the most potent CPE inhibition effect, which was stronger than that of the positive control ribavirin against H1N1, with an EC50 (mu M) of 2.57 +/- 0.45 along with higher selectivity.
Keywords: ABSOLUTE-CONFIGURATION; CONSTITUENTS; TRYPTOPHAN; PROLINE